Perception of local community in surrounding of human-elephant conflict area to elephant conservation and their habitat in sub-district of Lembah Seulawah, Aceh Besar - Abdullah Abdullah; M. Ali Sarong; Putri Hilmayanti (Biologi Edukasi: Jurnal Ilmiah Pendidikan Biologi, 2017)
Sumatran Elephant (Elephas maximus sumatranus) is one of Indonesia's biodiversity. This animal classified in endangered species. Habitat loss, degradation, habitat fragmentation and exploitation of resources due to human activities lead to the unavailability of habitat for wildlife. Fragmentation of wildlife habitat frequently cause loss of natural habitat. The purpose of this research are (1) to describe the Sumatran Elephant habitat disturbance, (2) to determine the extent of damage caused by the Sumatran Elephant and (3) to determine the local community perception sorrounding of human-elephant conflict area on the conservation of elephants and their habitats in Lembah Seulawah, Aceh Besar. Collecting data used descriptive research with quantitative approach and proportional sampling tehnique. The study was conducted in Lembah Seulawah, Aceh Besar in May 2016. The data collected using field survey, questionnaire and deep interview. Research data showed in descriptive and percentage. Analysis of the level of damage to the quality scale, and analysis of local community of perceptions using chi-square. The results of the study are (1) Disturbance plantation community in Lembah Seulawah between 0.5% - 2%, (2) Damage to habitat in Gampong Panca and Gampong Teuladan medium category, while Gampong Lamkubu is in lightweight category and (3) the public perception was good (X2count X2table, 35.54 16.9) and support to cponserve of sumatran elephant and their habitat.